Full scope 3D analysis of a VVER-1000 containment pressurization during a LB-LOCA by employing AutoCAD and GOTHIC code. (October 2022) - Kanik, Muhammet Enis; Noori-kalkhoran, Omid; Fernández-Cosials, Kevin; Gei, Massimiliano
Abstract: One of the main goals of severe accident management strategies is to maintain containment integrity to prevent radioactive release into the environment. As a result, containment internal loads need to be investigated during a postulated accident. In the present study, short-term containment thermal-hydraulic (TH) parameters of a VVER-1000/V446 reactor are analysed during a LB-LOCA. To achieve this goal, in the first step as-built 3D structure of VVER-1000/V446 containment was modelled in detail by using AutoCAD. The AutoCAD model has been processed to be prepared for GOTHIC 3D input. Meanwhile, an equivalent GOTHIC lumped parameter (LP) model is also prepared to validate the modelling procedure and results against the FSAR. Finally, LP profiles and 3D TH contour results of GOTHIC code were presented and discussed. LP results show a close agreement with FSAR reference and can approve the accuracy of the simulation procedure. 3D contours present all-coordinate detailed TH parameters versus time inside the containment. Spatial distribution of TH parameters and minor short-term effects of spray as Engineering Safety Features (ESFs) to tackle the containment pressurization can be evaluated by employing these contours. 3D simulation results can provide advantages for the precise locating and installation of ESFs in design and operation to achieve the highest efficiency in case of containment accident. Highlights: 3D simulation of Thermal-Hydraulic parameters inside VVER-1000 containment. As-built 3D modelling of a unique VVER-1000/V446 containment structure using CAD. The capability of detecting compartment hot spots using resulted 3D contours. Evaluating Lumped Parameter and 3D simulation methods pros and cons. Benchmarking the LP and volume-averaged 3D results against FSAR reference.